Forecasting the Economic Value of an Enterovirus 71 (EV71) Vaccine - Lee, Bruce Y. (2010)
Enterovirus 71 (EV71) is a growing public health concern, especially in Asia. A surge of EV71 cases in 2008 prompted authorities in China to go on national alert. While there is currently no treatment for EV71 infections, vaccines are under development. We developed a computer simulation model to determine the potential economic value of an EV71 vaccine for children (<5 years old) in China. Our results suggest that routine vaccination in China (EV71 infection incidence 0.04%) may be cost-effective when vaccine cost is $25 and efficacy ≥70% or cost is $10 and efficacy ≥ 50%. For populations with higher infection risk (≥ 0.4%), a $50 or $75 vaccine would be highly cost-effective even when vaccine efficacy is as low as 50%.